2014
DOI: 10.1038/aps.2014.113
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of capsaicin using MPEG-PCL nanoparticles

Abstract: Aim: To prepare a biodegradable polymeric carrier for oral delivery of a water-insoluble drug capsaicin (CAP) and evaluate its quality. Methods: CAP-loaded methoxy poly (ethylene glycol)-poly(ε-caprolactone) nanoparticles (CAP/NPs) were prepared using a modified emulsification solvent diffusion technique. The quality of CAP/NPs were evaluated using transmission electron microscopy, powder X-ray diffraction, differential scanning calorimetry and Fourier transform infrared techniques. A dialysis method was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 37 publications
(44 reference statements)
3
50
0
Order By: Relevance
“…[49] Previous studies have demonstrated that solid state interactions between the drug and the hydrophobic block, and the mobility of the hydrophobic block all govern the drug release rate. [46] LY has the fastest drug release from the three-drug NP followed by DTX and then EVR. This may be due to the relative hydrophobicities of these molecules and their potential interaction with the PCL domain.…”
Section: Accepted M Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…[49] Previous studies have demonstrated that solid state interactions between the drug and the hydrophobic block, and the mobility of the hydrophobic block all govern the drug release rate. [46] LY has the fastest drug release from the three-drug NP followed by DTX and then EVR. This may be due to the relative hydrophobicities of these molecules and their potential interaction with the PCL domain.…”
Section: Accepted M Manuscriptmentioning
confidence: 98%
“…This biphasic release pattern exhibited by PEG-PCL NP has been well documented in the literature. [46,47] The initial burst release is primarily driven by the desorption and the diffusion of surface adsorbed drug particles, while the secondary phase of drug release is driven by the erosion of the NP matrix and drug diffusion processes. The inner segment, PCL, is a biodegradable polyester that has a high crystallinity while the outer PEG shell increases the porosity in the PCL matrix and thereby allows the diffusion of drugs from the matrix into the buffer.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…According to the previous reports, mPEG-PCL copolymer has been synthesized by ring-opening polymerization of e-caprolactone, initiated by mPEG-5000 with Sn(Oct) 2 as a catalyst [26][27][28]. Briefly, pre-weighted amount of mPEG and e-caprolactone (w/w ¼ 1:2) were introduced into a dry twonecked flask containing Sn(Oct) 2 and then dissolved in an anhydrous toluene solution.…”
Section: Synthesis Of Mpeg-pcl Block Copolymermentioning
confidence: 99%
“…PCL NPs are characterized by a diameter lower than 100 nm and ability of passive targeting and sustained drug release (Kim et al 2015). What is more, over the last few years, a significant necessity emerged to evaluate PCL NPs possible pharmaceutical applications in drug delivery systems, due to their ability to transport variety of hydrophobic drugs and relatively lower cost of production and more satisfying biocompatibility (Peng et al 2015).…”
Section: Introductionmentioning
confidence: 99%